Orientation morphology evolution and mechanical properties of injection molded thermoplastic polyurethane - XIANG Ning; ZHANG Xiao-wen; GE Yong; DING Yao; ZHENG Meng-yao; YAN Yue (Cailiao gongcheng, 2021)
The effects of melt flow on the orientation evolution, residual stress and mechanical properties of thermoplastic polyurethane (TPU) during injection molding were studied by birefringence, small angle X-ray scattering (SAXS) and wide angle X-ray scattering (WAXS). The birefringence results show that the residual stress is decreased along the melt flow direction. The hard segments of TPU molecular chains are oriented along the melt flow direction, while the hard domains are oriented perpendicular to the melt flow direction according to the results of SAXS and WAXS. The tensile properties of TPU parts show obvious differences along the melt flow direction and perpendicular to the melt flow direction. The tensile strength of the middle region of the part is the highest because the orientation degree of hard segment and hard domain is the highest in the middle region of the part, and the orientation of hard segment and hard domain is helpful to improve the tensile strength.